Cultures in Collision: Traditional Knowledge and Euro-Canadian Governance Processes in Northern Land-Claim Boards - White, Graham (ARCTIC, 2009)
This paper analyzes how traditional knowledge (TK) is used by two of the co-management and regulatory boards established under the comprehensive land-claim agreements in Canada’s territorial North: the Nunavut Wildlife Management Board (NWMB) and the Mackenzie Valley Environmental Impact Review Board (MVEIRB). A comparison of the defining characteristics of Western “Weberian” bureaucracy, which sets the framework within which these and other boards operate, and central tenets of traditional northern Aboriginal culture highlights the oftentimes stark incompatibilities between what amount to different worldviews. Both boards are shown to have made substantial and sincere efforts at incorporating TK into their practices. The NWMB, with its wildlife-focused mandate, is better able to accommodate TK in its work than is the MVEIRB, which deals with complex legal regulatory issues. Both, however, are limited in their capacity to fully incorporate TK into their operations by the exigencies of the modern bureaucratic state. Le présent document analyse la manière dont les connaissances traditionnelles (CT) sont utilisées par deux des offices de cogestion et de réglementation fondés en vertu des accords exhaustifs de revendication territoriale dans le Nord canadien, soit l’office Nunavut Wildlife Management Board (NWMB) et l’office Mackenzie Valley Environmental Impact Review Board (MVEIRB). La comparaison des caractéristiques déterminantes de la bureaucratie « weberienne » occidentale, qui établit le cadre de fonctionnement de ces offices et d’autres offices, et des principes fondamentaux de la culture autochtone traditionnelle du Nord fait ressortir les incompatibilités parfois difficiles entre ce qui se résume à être des visions différentes du monde. Les deux offices ont fait des efforts considérables et sincères pour intégrer les connaissances traditionnelles à leurs pratiques. Le NWMB, avec son mandat axé sur la faune, est mieux en mesure de tenir compte des connaissances traditionnelles dans son travail que le ...